2009
DOI: 10.5194/bg-6-647-2009
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and natural CO<sub>2</sub> exchange through the Strait of Gibraltar

Abstract: Abstract. The exchange of both anthropogenic and natural inorganic carbon between the Atlantic Ocean and the Mediterranean Sea through Strait of Gibraltar was studied for a period of two years under the frame of the CARBOOCEAN project. A comprehensive sampling program was conducted, which was design to collect samples at eight fixed stations located in the Strait in successive cruises periodically distributed through the year in order to ensure a good spatial and temporal coverage. As a result of this monitori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 69 publications
10
77
0
Order By: Relevance
“…Lateral exchanges of carbon to surrounding seas are significant (e.g., Ait-Ameur and Goyet, 2006;Huertas et al, 2009;Schneider et al, 2010;Flecha et al, 2012) well constrained, similar to different methods for calculating C ant in the Mediterranean Overflow Water (MOW), which lead to different magnitudes and even direction of the net flux through the Strait of Gibraltar. In particular, it seems that the TrOCA method overestimates the C ant concentration in the MOW, leading to too large an export of C ant from the Mediterranean to the Atlantic.…”
Section: Present Knowledgementioning
confidence: 99%
“…Lateral exchanges of carbon to surrounding seas are significant (e.g., Ait-Ameur and Goyet, 2006;Huertas et al, 2009;Schneider et al, 2010;Flecha et al, 2012) well constrained, similar to different methods for calculating C ant in the Mediterranean Overflow Water (MOW), which lead to different magnitudes and even direction of the net flux through the Strait of Gibraltar. In particular, it seems that the TrOCA method overestimates the C ant concentration in the MOW, leading to too large an export of C ant from the Mediterranean to the Atlantic.…”
Section: Present Knowledgementioning
confidence: 99%
“…A Newtonian dumping term regulates the Atlantic buffer zone that is outside the Strait of Gibraltar (atl in Fig. 1), where the alkalinity and DIC concentrations are relaxed to the mean profiles derived from the data published by Huertas et al (2009) andDafner et al (2001).…”
Section: Model Setupmentioning
confidence: 99%
“…In addition, regressions based on local areas exist (SantanaCasiano et al, 2002;Huertas et al, 2009), some of which indicate a negative correlation between alkalinity and salinity in regions of freshwater (river) input (Luchetta et al, 2010). Few data, however, are available for the Mediterranean Sea, and as such, in this important basin the statistical spatial interpolation and extrapolation of existing information are critical.…”
Section: Introductionmentioning
confidence: 99%
“…Sabine and Tanhua (2010) compared the pros and cons of the different methods, but did not venture into making a full assessment. Studying CO 2 exchange through the Strait of Gibraltar, Huertas et al (2009) compared C * and TrOCA estimates of C ant , and found large differences with TrOCA estimating increases with depth. Reasoning from Mediterranean circulation patterns and dissolved CFC concentrations, they concluded that the TrOCA parameter values optimised in Touratier et al (2007) should be adapted for this location.…”
mentioning
confidence: 99%